Sooner safer happier : antipatterns and patterns for business agility - Smart, Jon; Berend, Zsolt; Ogilvie, Myles; Rohrer, Simon (IT Revolution, 2020)
"It's no secret that we are living in the Digital Age. Technology companies make up seven of the world's ten largest firms by market capitalization. And the key to their success is the key to all modern organizations. Jonathan Smart, business agility practitioner, thought leader, and coach, reveals the patterns and antipatterns that will help organizations from every industry deliver better value sooner, safer, and happier through high levels of engagement, inclusion, and empowerment. Through his decades of experience in the technology world, Smart provides business leaders with a blueprint for creating a world-class organization of the future. Through Agile and Lean ways of working, business leaders can empower teams to improve production, grow together, and create better services for their customers. These better ways of working have overflowed from the IT department to every corner of successful organizations, taking root in every industry from aerospace to accounting, insurance to shipping. This book is not about software development. It is not a book about the computer industry. This book is about applying agility across the entire organization. It's a book that will put you at the front of change and ahead of the competition"--